Pengetahuan dan Minat berhubungan dengan Keikutsertaan Ibu Hamil dalam Program Vaksinasi Covid-19 - Sumiaty Sumiaty; Hastuti Usman; Christina Entoh; Ni Ketut Hendriani; Sarliana Sarliana; Yuli Admasari (Poltekkes Kemenkes Palu, 2023)
Introduction: Pregnant women infected with Covid-19 are at risk of experiencing miscarriage and preterm birth. From a total of 232 pregnant women, 8 individuals (3.4%) have been vaccinated against Covid-19 at Kinovaro Primary Health Center. Objective: To identify factors associated with the participation of pregnant women in the Covid-19 vaccination program. Method: This study employed an analytical research design with a Cross-Sectional approach. The population consisted of all pregnant women in the working area of Kinovaro Primary Health Center. The sample size was 43 respondents, selected using consecutive sampling technique. The research instrument was a questionnaire, and data analysis included univariate and bivariate analyses using the chi-square test. Results: There is a significant association between knowledge and interest with the participation of pregnant women in the Covid-19 vaccination program (p value 0.000). There is no association between residential distance and the participation of pregnant women in the Covid-19 vaccination program (p value 0.56). Conclusion: There are two factors (knowledge and interest) that are associated with the participation of pregnant women in the Covid-19 vaccination program, and one factor (distance) that is not associated. Recommendations: Healthcare professionals are encouraged to enhance their efforts in providing effective education to individuals and families, especially pregnant women, to maintain a positive mindset and seek information about health, particularly regarding Covid-19 vaccination.